Clinical audit of knowledge and practice of epidural labour analgesia amongst obstetricians in South-West Nigeria (2010)
Epidural analgesia (EA) is the most ideal method for pain relief during labour. We sought to highlight the current knowledge and practice of the obstetricians regarding epidural labour analgesia (ELA). An audit was conducted amongst obstetricians in two teaching hospitals in the south west of Nigeria. Most of our respondents received lectures about ELA but about half of them rated the lectures as inadequate. Though 37.8 % and 53.3% of respondents are of the opinion that there is interference with labour and increased incidence of instrumentation following epidural analgesia in labour respectively, however 84.4% agreed that the technique is not associated with adverse neonatal or maternal outcome and 97.8% will prefer their patients having epidural labour analgesia. We are of the opinion that education regarding ELA, both during and after obstetric speciality training, be improved, and well-established interpersonal relationship between obstetricians and anaesthetists will be needed to achieve this.